OSbrca: A Web Server for Breast Cancer Prognostic Biomarker Investigation With Massive Data From Tens of Cohorts - Yan, Zhongyi; Wang, Qiang; Sun, Xiaoxiao; Ban, Bingbing; Lu, Zhendong; Dang, Yifang; Xie, Longxiang; Zhang, Lu; Li, Yongqiang; Zhu, Wan; Guo, Xiangqian (Frontiers in Oncology, 2019)
Exploiting potential prognostic mRNA biomarkers is to assist clinical management and treatment of breast cancer, which is the first life-threatening tumor in women worldwide. However, it is technically challenging for untrained researchers to process the high dimensional profiling data to screen and validate the potential prognostic values of genes of interests in multiple cohorts. Our aim is to develop an easy-to-use web server to facilitate the screening, developing and evaluating of prognostic biomarkers in breast cancers. Herein, we collected more than 7,400 cases of breast cancer with gene expression profiles and clinical follow-up information from TCGA and GEO data, and built an Online consensus Survival analysis web server for Breast Cancers, abbreviated OSbrca, to generate the Kaplan Meier survival plot with hazard ratio (HR) and log rank P value for given genes in an interactive way. To examine the performance of OSbrca, 128 previously published biomarkers of breast cancer were re-assessed their prognostic potency in OSbrca. In conclusion, it is highly valuable for biologists and clinicians to perform the preliminary assessment and validation of novel or putative prognostic biomarkers for breast cancers. OSbrca could be accessed at http://bioinfo.henu.edu.cn/BRCA/BRCAList.jsp.